Adapting corporate entrepreneurship assessment instrument for Romania - Cristian Vizitiu; Alexandru Agapie; Robert Paiusan; Shahrazad Hadad; Marian Nastase (South African Journal of Business Management, 2018)
Background: The study adapts the corporate entrepreneurship assessment instrument (CEAI), a notable North American psychometric instrument used to evaluate entrepreneurial culture, and investigates its construct validity scale, taking into account that psychometric instruments have limited cross-cultural portability. Objectives: We aim at identifying the perceived internal management key factors in the Romanian entrepreneurial culture (private sector) and applying CEAI to emergent economies. Method: The corporate entrepreneurship assessment instrument uses a 48-item Likert scale questionnaire to collect information from a large sample of employees working in different companies. The questions, seen as random variables, are then factor analysed in order to get a reduced more manageable structure. Factors are finally interpreted with respect to the entrepreneurial propensity of the business sector in study. The software used for statistical analysis was SPSS. Results: The survey conducted on 175 professionals from Romanian technology-based companies yielded a 10-factor structure for this particular business environment: reinforcement and work discretion, dynamic environment and decreased formalisation, delegation, time availability, strategic awareness, management support, stress, vertical communication, horizontal communication and knowledge sharing. Conclusion: The study provides a thorough understanding of the Romanian post-communist corporate culture, and, together with a similar analysis recently performed in South Africa, aims to create a clearer picture of cross-cultural portability of entrepreneurship psychometric instruments.
Keywords: 650